2000
DOI: 10.1007/s007950000022
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of denuded hepatic stellate cells and their subsequent myofibroblast-like transformation during the early stage of biliary fibrosis in the rat

Abstract: To investigate the early in vivo response of hepatic stellate cells in biliary fibrosis, we examined rat livers during the first 7 days after bile duct ligation using light microscopy, immunohistochemistry, electron microscopy, and immunoelectron microscopy. At day 1 after bile duct ligation, alpha-smooth muscle actin-positive fibroblasts appeared and then increased in number around the proliferating bile ductules. With time, the destruction of the external limiting plate became accentuated because of the inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 24 publications
2
37
0
Order By: Relevance
“…At early time points, combined expression of a-SMA and desmin was found at the interface of portal/septal ductules with the lobule. As it was previously shown by electron microscopy that at this time in BDL rats, fat dropletcontaining HSCs that were disconnected from the liver lobule (thus called denuded HSCs), congregated in the front of biliary fibrosis at the periportal fibrous tissue-lobular interface, 37 we may postulate that these cells comprised at least in part myofibroblastic HSCs. Nevertheless, time course analyses showed that the vast majority of a-SMA-labeled cells that co-localized with fibrosis became desmin-negative over time, suggesting that they derived mainly from portal mesenchymal cells distinct from HSCs, except for intralobular myofibroblastic HSCs detected in BDL cirrhotic liver.…”
Section: Discussionmentioning
confidence: 50%
“…At early time points, combined expression of a-SMA and desmin was found at the interface of portal/septal ductules with the lobule. As it was previously shown by electron microscopy that at this time in BDL rats, fat dropletcontaining HSCs that were disconnected from the liver lobule (thus called denuded HSCs), congregated in the front of biliary fibrosis at the periportal fibrous tissue-lobular interface, 37 we may postulate that these cells comprised at least in part myofibroblastic HSCs. Nevertheless, time course analyses showed that the vast majority of a-SMA-labeled cells that co-localized with fibrosis became desmin-negative over time, suggesting that they derived mainly from portal mesenchymal cells distinct from HSCs, except for intralobular myofibroblastic HSCs detected in BDL cirrhotic liver.…”
Section: Discussionmentioning
confidence: 50%
“…Molecular chaperones are necessary for folding of procollagen type I, and it has been documented that an increase in HSP47, a collagen-specific molecular chaperone, parallels the increase in collagen synthesis in various tissues (14,38,40,55). The number of translocons per cell must also increase during activation of HSCs, because rough ER becomes more prominent during their activation into myofibroblast-like cells (17,50). In our microarray study we detected upregulation of the Sec 10-like 1 gene and Sec 23 homolog B gene, encoding components of the protein secretion pathway.…”
Section: Discussionmentioning
confidence: 99%
“…An increased amount of microfilaments is seen underneath the plasma membrane, a feature of myofibroblasts or activated HSC. 2,[24][25][26] Activated HSC localize in close proximity to collagen fibers. In vivo, engulfed AB become phagosomes, and at a later stage, phagolysosomes that are readily identified as double membrane-bound intracytoplasmic organelles containing remnants of cell organelles, and chromatin derived from apoptotic cells.…”
Section: Phagocytosis Of Apoptotic Bodies Induces Nadphmentioning
confidence: 99%